Income effects of fodder and herd management on small-scale milk producers in the northern Peruvian Andes - Bernet, T.; León Velarde, C.U. (2000)
A linear programming model was used to analyze the effects of different herd and fodder management levels on agricultural income of small-scale mountain dairy farmers in northern Peru. Results demonstrate that fodder and herd management strongly impact farm profits. There exists considerable potential to improve this situation, as many farmers in the study region are deficient in their fodder and herd management. When moving from average to high management levels, farmers could double their farm profits. In general, high mortality rates, long calving intervals, and inefficient fodder storage practices depress farmers' incomes most. Because of feeding deficiencies, especially in the dry season, recommended extension activities primarily must emphasize fodder storage and improved pasture management, to subsequently also enhance better herd management practices.